2006
DOI: 10.1148/rg.264055125
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Renal Lymphoma: Patterns of Disease with Pathologic Correlation

Abstract: Extranodal spread of lymphoma often affects the genitourinary system, with the kidneys being the most commonly involved organs. Contrast material-enhanced computed tomography (CT) remains the modality of choice for the detection, diagnosis, staging, and monitoring of renal lymphoma. Magnetic resonance (MR) imaging is particularly useful in patients in whom intravenous administration of iodinated contrast material is contraindicated. Ultrasonography (US), although very valuable for diagnosing lymphoma in the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
0
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(145 citation statements)
references
References 47 publications
(77 reference statements)
3
126
0
15
Order By: Relevance
“…In most of the cases it is secondary and occurs by hematogenous spread or by direct extension of the disease from a retroperitoneal mass. Villa et al concluded that there is a high incidence of central nervous system relapse in patients with DLBCL and kidney involvement at diagnosis [18][19][20]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the cases it is secondary and occurs by hematogenous spread or by direct extension of the disease from a retroperitoneal mass. Villa et al concluded that there is a high incidence of central nervous system relapse in patients with DLBCL and kidney involvement at diagnosis [18][19][20]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This modality not only depicts the renal lesions, but also aids in the identification of extrarenal extension to adjacent anatomic structures and thus can determine the systemic spread of the disease. 14 Both clinically and pathologically, they can be mistaken for carcinomas of the kidney. In the series by Ferry et al, 6 the majority of patients had unilateral disease and B-cell lineage tumors.…”
Section: Discussionmentioning
confidence: 99%
“…BT'de çoklu kitle olabileceği gibi soliter tümör olarak görülüp RHK ile karışabilir. Bazı hastalarda böbrekte diffüz tutulum ve böbreği dışarıdan invaze eden bir kitle olarak da görülebilir (26). Böbrek lenfomasından şüphelenmemizi sağlayacak klinik bulgular büyük retroperitoneal LAP'lar, splenomegali ve böbrek ile ilişiksiz alanlarda tespit edilen LAP`lardır.…”
Section: Nöroendokrin Karsinoma (Küçük Hücreli Karsinoma)unclassified